Modeling and simulation of blood flow under the influence of radioactive materials having slip with MHD and nonlinear mixed convection - Sidra Afzal; Mubashir Qayyum; Muhammad Bilal Riaz; Adam Wojciechowski (Alexandria Engineering Journal, 2023)
Radioactive materials are widely in industry, nuclear plants and medical treatments. Scientists and workers in these fields are mostly exposed to such materials, and adverse effects on blood and temperature profiles are observed. In this regard, objective of the current study is to model and simulate blood based nanofluid with three very important radioactive materials, named as Uranium dioxide (UO2), Thorium dioxide (ThO2) and Radium (Rd). In this modeling blood based nanofluid is considered under the influence of magneto hydrodynamic effect, non-linear mixed convection and thermal radiation, Joule heating, along with velocity and temperature slip. A three-dimensional fluid model is considered in bounded domain to justify flow geometry in arteries. System of partial differential equations are converted to highly nonlinear coupled ordinary differential equations by using suitable transformations. The obtained system is solved numerically using Fehlberg Runge–Kutta algorithm. Validity and convergence of the obtained solutions are confirmed through residual errors, numerical uncertainties and comparison with experimental data. Moreover, effect of pertinent fluid parameters on the velocity (radial, axial, tangential) and temperature profiles of blood flow are analyzed graphically. Furthermore, Skin friction and Nusselt number are also analyzed graphically against volume fraction of involved radioactive materials for the case of UO2,ThO2 and Rd comparatively. Analysis reveals that increase in volume fraction of radioactive elements results in increased blood flow through walls in both radial and tangential directions. In case of slip at fluid solid-interface, the highest skin fraction is observed in case of Radium nanoparticles.